A Comparison of the Rate of Gastrointestinal Bleeding in Patients Taking Non‐Vitamin K Antagonist Oral Anticoagulants or Warfarin. (May 2017) - Cangemi, David J; Krill, Timothy; Weideman, Rick; Cipher, Daisha J; Spechler, Stuart J; Feagins, Linda A
Abstract : Objectives: Early reports suggested that the risk of gastrointestinal bleeding (GIB) was higher for patients on non‐vitamin K antagonist oral anticoagulants (NOACs) than for those on warfarin. We compared the incidence of GIB in our patients on NOACs with those on warfarin. Methods: We used our VA pharmacy database to identify patients taking NOACs (dabigatran, rivaroxaban, and apixaban) or warfarin between January 2011 and June 2015, and used the VistA system to identify those who were hospitalized for GIB. We included only patients with clinically significant GIB, defined as documented GI blood loss with a hemoglobin drop ≥2 g/dl, hemodynamic instability, and/or need for endoscopic evaluation, angiography, or surgery. Results: We identified 803 patients on NOACs and 6, 263 on warfarin. One hundred and fifty‐eight patients on warfarin had GIB (2.5%), compared with only five patients (0.6%) on NOACs (odds ratio=4.13; 95% confidence interval: 1.69–10.09). Blood transfusion for GIB was significantly more common in patients on warfarin than on NOACs (64.6% vs. 20%, P =0.04). Within 90 days of GIB hospitalization, 12 patients (7.6%) in the warfarin group died, whereas there were no deaths in the NOAC group. Conclusions: In our patients, the incidence of GIB for those on warfarin was more than four times that for those on NOACs. Blood transfusions for GIB were more common in warfarin patients, and no NOAC patients died of GIB. In contrast to early reports, our findings suggest that the risk of GIB and subsequent complications is considerably lower for patients on NOACs than for patients on warfarin.